CORPORATION AUDITING REQUIREMENTS UNDER THE GERMAN COMMERCIAL LAW. - Voss, Wilhelm (The Accounting Review, 1930)
Abstract In almost all German corporations it is at present customary to check up all accounting statements especially the annual balance sheet and profit and loss statement. This work is done by separate auditors or auditing companies. The law, however, does not as yet require an audit. According to the law at present the Supervisory Council as the controlling agent of the corporation is required to supervise all phases of the business including the examination of the financial statements and annual closing entries in order to report thereon at the general stockholders' meeting. The audit function is, therefore, in accordance with the present German law, included in the general control function of the Supervisory Council. The appointment of separate auditors is according to law necessary only in special cases. The Board of Directors in the cases under Section 266, is to allow the auditors to examine the books and papers of the company and also the cash, securities, and goods as well.